Small Bowel Capsule Endoscopy: Experience from a single large tertiary care centre - Singla, Neeraj; Inavolu, Pradev; Jagtap, Nitin; Singh, Aniruddha Pratap; Kalapala, Rakesh; Memon, Sana Fathima; Katukuri, Gowtham Reddy; Pal, Partha; Nabi, Zaheer; Ramchandani, Mohan; Lakhtakia, Sundeep; Banerjee, Rupa; Reddy, Palle Manohar; Tandan, Manu; Reddy, Nageshwar (Endoscopy International Open, 2023)
Background and study aims Capsule endoscopy (CE) has transformed examination of the small bowel (SB), once considered a dark continent. The present study aimed to describe the indications, diagnostic yield, practical issues and complications of CE in one of the largest tertiary center in India.Patients and methods This retrospective analysis from a prospectively maintained database, conducted from January 2013 to June 2021 included 1155 CEs performed during this period. Patient medical records were reviewed for indications, results, and complications of CE.Results A total of 1154 patients (809 males and 345 females), mean age 53 years (range 6–87 years), one capsule got stuck in the esophagus, were included in the study. Active SB bleeding had no effect on SB transit time (324.7±161 minutes, n = 137 patients with active bleed vs 310.6±166.9 minutes, n = 1017 patients without active bleed; P = 0.35). The indication and diagnostic yield (DY) of CE were potential overt SB bleed (68.6% & 43.9%), potential occult SB bleed (8.2% and 40%), chronic diarrhea (7.9% and 28.4%), abdominal pain (6.5% and 21.3%), anemia (5.9% and 57.9%), and suspected/known case of Crohn’s disease (2.3% & 56.5%) respectively. The DY for patients with age ≥60 years was similar to those with age < 60 years (61.9% vs. 51.8% respectively; P = 0.4). 21 patients (1.8%) had capsule retention of which six (0.5%) had to be referred for surgery.Conclusions CE is a safe and effective investigation with ever increasing range of indications. Potential SB bleed remains the most common indication for CE with high detection rate.